2016
DOI: 10.1590/s1984-29612016036
|View full text |Cite
|
Sign up to set email alerts
|

Hemostatic assessment of dogs associated with hepatic parasite load of Leishmania infantum chagasi

Abstract: Leishmania infantum chagasi liver parasite load was compared to hemostatic abnormalities, as well as to clinical, laboratorial, and histopathological findings in dogs with visceral leishmaniasis. The liver parasite load of 30 dogs L. infantum chagasi naturally-infected was evaluated by quantitative real-time PCR and the results were compared with serum biochemistry and primary and secondary hemostasis findings. Moreover, hepatic histological lesions were described in these dogs. Prolonged bleeding time, prothr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
2
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 14 publications
0
2
0
3
Order By: Relevance
“…This might be briefly explained with the relationship among inflammation and coagulation (change), or it may be suggested that during clinical disease state in CVL, hemorrhagic diathesis might occur, not only due to the existence of the parasite but also related to inflammation, immunocompetence and probably because of hepatic/renal failure. 29…”
Section: Discussionmentioning
confidence: 99%
“…This might be briefly explained with the relationship among inflammation and coagulation (change), or it may be suggested that during clinical disease state in CVL, hemorrhagic diathesis might occur, not only due to the existence of the parasite but also related to inflammation, immunocompetence and probably because of hepatic/renal failure. 29…”
Section: Discussionmentioning
confidence: 99%
“…In most instances, published data describing coagulation alterations in dogs infected by one or more vector-borne pathogens derive from case reports, cross-sectional studies, or naturally infection studies involving single pathogens [7,10,29,34]. Bleeding disorders such as epistaxis, haematuria and haemorrhagic diarrhoea has been reported in dogs with vector-borne diseases [2,6].…”
Section: Discussionmentioning
confidence: 99%
“…As células mononucleares infectadas migram pela circulação sanguínea atingindo diversos órgãos como o baço, linfonodos e tecidos como pele e intestino, além do tecido hematopoético, estimulando o sistema imune de forma localizada e sistêmica. Neste sentido, L. infantum circula pelo tecido hepático e induz infiltrado inflamatório por decorrente de fatores quimiotáticos liberados pelas CKs parasitadas (Rodrigues et al, 2019) e CEH, causando hepatite periportal e degeneração de hepatócitos (Souza et al, 2014;Torres et al, 2016). Em resposta a infecção, o fígado torna-se aumentado (hepatomegalia) e congesto associado à reação inflamatória granulomatosa crônica, caracterizada por numerosos granulomas hepáticos intralobulares (Giunchetti et al, 2008;Souza et al, 2014).…”
Section: Resposta Hepática Aos Agentes Infecciososunclassified
“…Na babesiose, anaplasmose e leishmaniose canina, além das alterações histológicas, foram relatados aumentos nas concentrações séricas das enzimas hepáticas alanina aminotransferase (ALT) e fosfatase alcalina (FA) (Chirek et al, 2018;Fraga et al, 2011;Torres et al, 2016). Essas enzimas estão presentes no citoplasma e membrana dos hepatócitos podendo, então, indicar lesão celular uma vez que elas estão alteradas.…”
Section: Resposta Hepática Aos Agentes Infecciososunclassified
See 1 more Smart Citation